Looking into Enteric Virome in Patients with IBD: Defining Guilty or Innocence?. Issue 8 (14th June 2017) - Lopes, Susana; Andrade, Patricia; Conde, Silvia; Liberal, Rodrigo; Dias, Cláudia C.; Fernandes, Salomão; Pinheiro, Jorge; Simões, Joana S.; Carneiro, Fátima; Magro, Fernando; Macedo, Guilherme
Abstract : Background: Although there is some evidence suggesting that certain viruses may be involved in the onset of inflammatory bowel disease (IBD), data regarding viral prevalence and viral load in blood and mucosa of patients with IBD are scarce. The main aim of this study is to evaluate the prevalence and viral load of common Epstein–Barr virus (EBV), cytomegalovirus (CMV), and human herpes virus 6 in blood and mucosa of adult patients with endoscopic active IBD. Methods: From January to December 2014, ulcerative colitis and Crohn's disease patients with active endoscopic disease were consecutively enrolled. Subjects undergoing colonoscopy for colorectal cancer screening served as healthy controls (HCs). Paired blood and mucosal samples from each patient and HC were collected for EBV, CMV, and human herpes virus 6 quantitative real time polymerase chain reaction assessment of the viral load. Results: One hundred forty-five subjects were included; 95 IBD patients with active endoscopic disease (43 ulcerative colitis and 52 Crohn's disease) and 50 healthy subjects. CMV and EBV DNA were detected more frequently in the mucosa of patients with IBD compared with HCs (CMV P = 0.017; EBV P < 0.001), irrespective of IBD type. The frequency of human herpes virus 6 DNA detection both in the blood and in the mucosa did not differ between patients with IBD and HCs. EBV median viral load was similar in the inflamed and noninflamed mucosa was not affected by the use of immunomodulators and/or anti–tumor necrosis factor alpha agents, and did not correlate with endoscopic disease activity. Conclusions: EBV, and to a lesser extent CMV, were more prevalent in patients with IBD than in HCs. Mucosal viral load was not influenced by the therapeutic regimen, did not differ between inflamed and noninflamed mucosa, and did not seem to be influenced by the endoscopic activity of the disease, suggesting that EBV may be more involved in the onset of IBD than in its severity and clinical evolution.